PENGARUH ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR DAN ORIENTASI PEMBELAJARAN TERHADAP KEUNGGULAN BERSAING DAN KINERJA USAHA (Studi Pada Usaha Kecil Pengolah Makanan di Kota Palembang) - Rini Rini; Lisnini Lisnini; Fetty Maretha; Yulia Pebrianti (Politeknik Negeri Sriwijaya, 2020)
The relationship between entrepreneurial orientation, market orientation, learning orientation, competitive advantage and business performance especially food processing small businesses is interesting to study. Food processing small businesses in Palembang are the object of research with a sample of 179 people. Path analysis is used in this study to measure the amount of influence between variables. The findings of the study show that the entrepreneurial orientation variable has a significant effect on competitive advantage. Market orientation variable has no significant effect on competitive advantage. The learning orientation variable has a significant effect on competitive advantage. The competitive advantage variable has a significant effect on business performance. The results of this study can contribute to small businesses in improving business excellence and performance.